Continued follow-up of the free margin running suture technique for mitral repair. (7th May 2020) - Agnino, Alfonso; Graniero, Ascanio; Roscitano, Claudio; Villari, Nicola; Marvelli, Antonino; Verhoye, Jean-Philippe; Anselmi, Amedeo
Abstract: OBJECTIVES: The free margin running suture (FMRS) technique was recently proposed to treat complex degenerative mitral lesions. Limited follow-up data are available. We evaluated the midterm reliability of this technique and the associated mitral valve parameters using rest/stress echocardiography. METHODS: One-hundred-eight consecutive patients at 2 European centres were included. Prospective follow-up was performed (266.1 patient-years, average duration 2.5 ± 2.5 years). Echocardiographic scans at rest were obtained for all patients at hospital discharge and at follow-up. Stress echocardiography was also performed in 17 patients. RESULTS: There were no operative deaths. FMRS was performed through a right minithoracotomy in 86.1% of patients, with a robotic-assisted technique in 5.6% and through a sternotomy in 8.3%. Bileaflet disease was noted in 31.4%. One patient (0.9%) presented a 2+/4+ residual mitral regurgitation at discharge; lower-degree or no residual regurgitation was noted in the remaining patients. At the follow-up examination, 1 patient (0.9%) presented with a 2+/4+ mitral regurgitation. Coaptation length at discharge versus that at follow-up was 1.3 ± 0.2 vs 1.3 ± 0.1 cm ( P  = 0.13); the average transmitral gradient was 4.8 ± 1.5 vs 3.5 ± 0.9 mmHg ( P  < 0.001). In a subpopulation, follow-up echocardiography indicated that the average transmitral gradient at rest versus that at peak effort was 3.2 ± 0.7 vs 5.1 ± 1.3 mmHg ( P  < 0.001), with no appearance of significant mitral regurgitation and marginally significant increases in pulmonary artery systolic pressures ( P  = 0.049). CONCLUSIONS: Data indicate effectiveness and reproducibility of FMRS, with stability of valve function at midterm. FMRS was also associated with promising outcomes in diastolic performance both at rest and during exercise.